Ensinando com respeito: pedagogia inclusiva para regentes corais - Vladimir Silva; Laís Lorrany Andrade; José Adriano de Sousa Lima Júnior; Daniel Berg Cirilo Alves; Anderson Maurício do Nascimento (Orfeu)
Resenha da obra: SIECK, Stephen. Teaching with respect: inclusive pedagogy for choral directors. New York: Hal Leonard, 2017.